Cosine Exponential Formulation/Real Domain/Proof 4

From ProofWiki
Jump to navigation Jump to search

Theorem

$\cos z = \dfrac {\map \exp {i z} + \map \exp {-i z} } 2$


Proof

Consider the differential equation:

$(1): \quad D^2_x f \left({x}\right) = - f\left({x}\right)$

subject to the initial conditions:

$(2): \quad f \left({0}\right) = 1$
$(3): \quad D_x f \left({0}\right) = 0$


Step 1

We will prove that $y = \cos x$ is a specific solution of $(1)$.

\(\displaystyle y\) \(=\) \(\displaystyle \cos x\)
\(\displaystyle D^2_x y\) \(=\) \(\displaystyle D^2_x \cos x\) taking second derivative of both sides
\(\displaystyle \) \(=\) \(\displaystyle D_x \left({- \sin x}\right)\) Derivative of Cosine Function
\(\displaystyle \) \(=\) \(\displaystyle - D_x \left({\sin x}\right)\) Derivative of Constant Multiple
\(\displaystyle \) \(=\) \(\displaystyle -\cos x\) Derivative of Sine Function
\(\displaystyle \) \(=\) \(\displaystyle -y\)

Thus $y = \cos x$ fulfils $(1)$.


Then from Cosine of Zero is One:

$\cos 0 = 1$

Thus $y = \cos x$ fulfils $(2)$.


Then:

\(\displaystyle D_x \cos 0\) \(=\) \(\displaystyle - \sin 0\) Derivative of Cosine Function
\(\displaystyle \) \(=\) \(\displaystyle 0\) Sine of Zero is Zero

Thus $y = \cos x$ fulfils $(3)$.

So $y = \cos x$ is a specific solution of $(1)$.

$\Box$


Step 2

We will prove that $z = \dfrac {e^{i x} + e^{-i x} } 2$ is a specific solution of $(1)$.

\(\displaystyle z\) \(=\) \(\displaystyle \frac {e^{ix} + e^{-ix} } 2\)
\(\displaystyle D^2_x z\) \(=\) \(\displaystyle D^2_x \left({\frac {e^{i x} + e^{-i x} } 2}\right)\) taking second derivative of both sides
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \left({D^2_x e^{i x} + D^2_x e^{-i x} }\right)\) Linear Combination of Derivatives
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \left({i D_x e^{i x} - i D_x e^{-i x} }\right)\) Derivative of Exponential Function
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \left({i^2 e^{i x} - i \left({-i}\right) e^{-i x} }\right)\) Derivative of Exponential Function
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 2 \left({- e^{i x} - e^{-i x} }\right)\) $i^2 = -1$
\(\displaystyle \) \(=\) \(\displaystyle -\frac {e^{i x} + e^{-i x} }2\)
\(\displaystyle \) \(=\) \(\displaystyle -z\)

Thus $z = \dfrac {e^{i x} + e^{-i x} } 2$ fulfils $(1)$.


Then:

\(\displaystyle \frac {e^{i \times 0} + e^{-i \times 0} } 2\) \(=\) \(\displaystyle \frac {1 + 1} 2\) Exponential of Zero
\(\displaystyle \) \(=\) \(\displaystyle 1\)

Thus $z = \dfrac {e^{i x} + e^{-i x} } 2$ fulfils $(2)$.


Then:

\(\displaystyle \left.{D_x \frac {e^{i x} + e^{-i x} } 2}\right\vert_{x \mathop = 0}\) \(=\) \(\displaystyle \left.{\frac {i e^{i x} - i e^{-i x} } 2}\right\vert_{x \mathop = 0}\) Derivative of Exponential Function
\(\displaystyle \) \(=\) \(\displaystyle \frac {i - i} 2\) Exponential of Zero
\(\displaystyle \) \(=\) \(\displaystyle 0\)

Thus $z = \dfrac {e^{i x} + e^{-i x} } 2$ fulfils $(3)$.

So $z = \dfrac {e^{i x} + e^{-i x} } 2$ is a specific solution of $(1)$.

$\Box$


We have shown that $y$ and $z$ are both specific specific solutions of $(1)$

But a specific solution to a differential equation is unique.

Therefore $y = z$.

That is:

$\cos x = \dfrac {e^{i x} + e^{-i x} } 2$

$\blacksquare$